2016
DOI: 10.1002/jmor.20548
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone of precocials at birth; Are they prepared to run for the wolf(f)?

Abstract: Bone is a dynamic tissue adapting to loading according to “Wolff's law of bone adaptation.” During very early life, however, such a mechanism may not be adequate enough to adapt to the dramatic change in environmental challenges in precocial species. Their neonates are required to stand and walk within hours after birth, in contrast to altricial animals that have much more time to adapt from the intrauterine environment to the outside world. In this study, trabecular bone parameters of the talus and sagittal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…Trabecular bone was quantitatively determined in manually drawn volumes of interest (VOIs) only including trabecular bone. Selected VOIs were in line with previous work (Gorissen et al, 2016). The tibial VOI contained the trabecular bone of the dorsal 25% of the sagittal ridge.…”
Section: Sample Preparationmentioning
confidence: 97%
See 3 more Smart Citations
“…Trabecular bone was quantitatively determined in manually drawn volumes of interest (VOIs) only including trabecular bone. Selected VOIs were in line with previous work (Gorissen et al, 2016). The tibial VOI contained the trabecular bone of the dorsal 25% of the sagittal ridge.…”
Section: Sample Preparationmentioning
confidence: 97%
“…However, precocial animals need to stand and outrun predators within hours after birth. To withstand the forces associated with this, foetal bone development has shown to be anticipative, reflecting future rather than past function, both in calves and foals (Gorissen et al, 2016). This phenomenon, which is possibly based on a genetic blueprint, seems general as it has been described in several other precocial species (Skedros et al, 2004; and even in altricial man (Cunningham & Black, 2009).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In 1892, Wolf indicated that mechanical stress determines bone growth and remodeling [10]. In 1953, Yasuda revealed that bending the long tubular bone is related with the development of electric currents and this instance is defined as piezoelectric phenomenon [11].…”
Section: Basic Knowledge Of Pemfs For Bone Repairmentioning
confidence: 99%